If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x(6)=x+14+8x+9+x+17
We move all terms to the left:
5x(6)-(x+14+8x+9+x+17)=0
We add all the numbers together, and all the variables
5x6-(10x+40)=0
We add all the numbers together, and all the variables
5x^6-(10x+40)=0
We get rid of parentheses
5x^6-10x-40=0
We do not support expression: x^6
| 8x+5=5x+14=13 | | 3x+65=6x+15 | | x+89=85 | | X+24=8+7x | | 8x+5=5+14=13 | | 4(3x-5)=2(6x-10) | | X+15+3x-6+31=180 | | -2-21+4x=3-2(13-2x) | | 4a−6=9+a | | 23x+6=24x+1 | | 3x=x=6 | | 5(x-3)+2x+7=5x+6 | | 72.46+-88.1=x | | k+11=−3k−25+2k | | 8x+5x=5x+14=13 | | 6/16x+2(5+4)=-2+3/8x+20 | | 5(X-3)+7=5x+6 | | 5x=10x+34 | | 2(k-7)=5k | | 4p+1=-5 | | 10k+18=8k+4 | | r+31/2=42/3 | | -1/4x+6=2/3x-28 | | 86+x/3=90 | | 1-1k=6-2k | | X+870=7x | | 10x+10=15x-5=180 | | S=r0 | | (-3x+5)+2(x-3)=-8 | | 19=14=k | | 3b+2-5b=-12 | | 2m-3(m-1)=-3 |